Development of a novel cannabinoid-loaded microemulsion towards an improved stability and transdermal delivery - Park, Chulhun; Zuo, Jieyu; Somayaji, Vijay; Lee, Beom Jin; Löbenberg, Raimar (International Journal of Pharmaceutics, 2021)
The aim of this study was to develop a stable microemulsion (ME) for transdermal delivery of tetrahydrocannabinolic acid (THCA) and cannabidiolic acid (CBDA). The lipid-based vehicles were selected by screening cannabinoid solubility and the emulsifying ability of surfactants. Pseudo-ternary phase diagrams were constructed by formulation of cannabinoids with Capryol® 90 as oil phase, Tween® 80, Solutol® HS15, Procetyl® AWS, and Cremophor® RH40 as surfactants, ethanol as cosurfactant, and distilled water as the aqueous phase. A significant improvement in transmembrane flux (Jss), permeability coefficient (Kp), and enhancement ratio (ER) was found in one system compared to other formulations. This ME consisted of 1.0% (w/w) of cannabinoids, 5% (w/w) of Capryol® 90, 44% (w/w) Smix (2:1, Procetyl® AWS and Ethanol) and 50.0% (w/w) of distilled water. Additionally, the effects of pH on the permeation of the cannabinoids were investigated. Based on the pH value THCA and CBDA-loaded ME exhibited the highest permeation at pH 5.17 and pH 5.25. After storing the pH-adjusted P2 ME and the optimized P2 ME for 180 days at 4℃ and 25℃, the content of cannabinoids was over 95%. Consequently, the cannabinoid-loaded ME system is a promising option for solubilizing and stabilizing lipophilic drugs like cannabinoids and utilize them for transdermal delivery.
Keywords: Administration, Cutaneous; Cannabinoids; Emulsions; Skin; Solubility; Surface-Active Agents; Acidic cannabinoids; Cannabidiolic acid; Cannabinoids; Lipid-based vehicle; Microemulsion; Tetrahydrocannabinolic acid; Transdermal delivery